1999
DOI: 10.1023/a:1008345901178
|View full text |Cite
|
Sign up to set email alerts
|

Combined sequential approach in locally advanced breast cancer

Abstract: SummaryBackground: The interaction between primary and adjuvant chemotherapy is a crucial point in the treatment of locally advanced breast cancer.Objective: To evaluate the therapeutic efficacy of a sequential treatment with primary anthracyclines and adjuvant CMF in this patient subset.Design: Prospective cohort study.Patients: Eighty-eight breast cancer patients, stage T3b-T4 abc, N 0 -2> M o .Results: From February 1991 to July 1994, 88 consecutive patients with locally advanced breast cancer were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In published studies, approximately 23%-32% of patients for whom the initial surgery would be a mastectomy are able to undergo BCT following PST [3][4][5][6]85]. In the NSABP B-18 trial, 67% of patients underwent BCT after neoadjuvant chemotherapy, compared with 60% of the group that received postoperative adjuvant treatment [3][4][5].…”
Section: Challenges Of Rt After Pst Bct After Pst In Locally Advancedmentioning
confidence: 99%
See 1 more Smart Citation
“…In published studies, approximately 23%-32% of patients for whom the initial surgery would be a mastectomy are able to undergo BCT following PST [3][4][5][6]85]. In the NSABP B-18 trial, 67% of patients underwent BCT after neoadjuvant chemotherapy, compared with 60% of the group that received postoperative adjuvant treatment [3][4][5].…”
Section: Challenges Of Rt After Pst Bct After Pst In Locally Advancedmentioning
confidence: 99%
“…With short follow-up, recurrence rates of 5% or less are observed. However, studies with follow-up of 52 months, 85.5 months, and 124 months reported recurrence rates of 14%, 19%, and 23%, respectively [9, 85,88].…”
Section: Challenges Of Rt After Pst Bct After Pst In Locally Advancedmentioning
confidence: 99%
“…In a retrospective analysis of 100 patients, Victor et al (1999) correlated the presence of IBC and four or more involved axillary nodes with poorer outcome. Their conclusions were supported by Gardin et al (1995) in an analysis of 125 patients, and by others as well (Sanchez-Forgach et al, 1992;Kuerer et al, 1998;Zambetti et al, 1999). The clinical size of the primary tumour (Valagussa et al, 1990;Fein et al, 1994) as well as the clinical nodal status (Valagussa et al, 1990) were also found to correlate with outcome.…”
Section: Discussionmentioning
confidence: 76%
“…New data and the newest treatments available indicate the need to re-think our general approach to endocrine therapy and endocrine prevention (Howell et al 2001). This is of particular interest today because the results of new combined therapies, including chemotherapy, endocrine therapy and radiotherapy modalities, have also been reported (Crump et al 1997, Brain et al 1999, Zambetti et al 1999, Tan et al 2001, Vicini et al 2001.…”
Section: Mechanism and Tolerability Of Hormone Therapies In Breast Camentioning
confidence: 99%